while using the zero product property to find the values of X that make the quadratic equation (X +3) ( X +4 )equals zero

1 answer

To find the values of X that make the quadratic equation (X + 3)(X + 4) equal to zero, we can set each factor equal to zero and solve for X:

X + 3 = 0
X = -3

X + 4 = 0
X = -4

Therefore, the values of X that make the equation (X + 3)(X + 4) equal to zero are X = -3 and X = -4.
Similar Questions
    1. answers icon 1 answer
  1. The Zero Product Property Quick Check1 of 51 of 5 Items Question Use the table to answer the question. (x+3)(x+4)=0 x−3=0
    1. answers icon 1 answer
  2. The Zero Product Property Quick Check1 of 51 of 5 Items Question Use the table to answer the question. (x+3)(x+4)=0 x−3=0
    1. answers icon 1 answer
    1. answers icon 1 answer
more similar questions